2013
DOI: 10.1002/lt.23722
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and long-term risk of de novo malignancies after liver transplantation with implications for prevention and detection

Abstract: The goal of this study was the characterization of long-term cancer risks after liver transplantation (LT) with implications for prevention and detection. Site-specific cancer incidence rates and characteristics were compared retrospectively for 2000 LT patients from a single institution (January 1, 1983 to December 31, 2010) and the general German population with standardized incidence ratios (SIRs); the total follow-up at December 31, 2011 was 14,490 person-years. The cancer incidence rates for the LT recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 35 publications
5
74
4
Order By: Relevance
“…14 A Europe-wide analysis undertaken by Eurotransplant concluded that the risk of de novo cancer for liver transplant recipients was very similar to the Australian data with an SIR of 1.94 (CI:1.53-2.44). 12 Lung cancer, colorectal cancer, lymphoma, renal cell carcinoma, thyroid cancer, and vulvar cancers were significantly increased in this cohort. In the United States, an analysis of 175 732 organ transplant recipients of which 37 888 received a liver allograft, were compared with the general US population using 14 US regional cancer registries.…”
Section: De Novo Cancersmentioning
confidence: 71%
See 1 more Smart Citation
“…14 A Europe-wide analysis undertaken by Eurotransplant concluded that the risk of de novo cancer for liver transplant recipients was very similar to the Australian data with an SIR of 1.94 (CI:1.53-2.44). 12 Lung cancer, colorectal cancer, lymphoma, renal cell carcinoma, thyroid cancer, and vulvar cancers were significantly increased in this cohort. In the United States, an analysis of 175 732 organ transplant recipients of which 37 888 received a liver allograft, were compared with the general US population using 14 US regional cancer registries.…”
Section: De Novo Cancersmentioning
confidence: 71%
“…Single-center cohort studies have also proved useful, but the number of life years of follow-up after transplant are usually insufficient for detailed analyses, though some specific inferences can be made. 11 Analyses of de novo cancer in liver transplant recipients have now followed the renal transplant methodologies, and there are publications from the European, 12 Australian, 13,14 and US registry experiences. 9 In their analysis of 1926 Australian Liver transplant recipients followed between 2.2 and 10 years after transplant (median, 6 y), Na and associates 13 compared a sex-and age-matched general Australian population and noted an increased Standardized Incidence Ratio (SIR) of 2.20 (confidence interval (CI) 1.87-2.57).…”
Section: De Novo Cancersmentioning
confidence: 99%
“…10 Schrem and associates reported that cancer incidence rates for liver transplant recipients were almost twice as high as those for an age-matched and sex-matched general population. 11 In another study from the United States, the authors showed a statistically significant increased risk for oropharyngeal cancer when they looked at several cancer types and compared them with the general population. 9 Recent studies have shown that at all tumor groups, especially skin cancers and lymphomas have a 10-fold increased risk when compared with the agematched and sex-matched general population.…”
Section: Discussionmentioning
confidence: 99%
“…Both microsatellite analysis and fluorescent in situ hybridization revealed the recipient origin of the tumor, potentially due to tissue chimerism. [4,5].…”
Section: Case Report Abstractmentioning
confidence: 99%